2010
DOI: 10.1586/ern.10.51
|View full text |Cite
|
Sign up to set email alerts
|

Rufinamide: a new antiepileptic drug treatment for Lennox–Gastaut syndrome

Abstract: Lennox-Gastaut syndrome is a relatively rare epilepsy syndrome that usually begins in early-mid childhood and is characterized by multiple seizure types, particularly generalized seizures, which are often resistant to antiepileptic drug medication. Rufinamide is a new antiepileptic drug approved as adjunctive therapy to treat seizures in Lennox-Gastaut syndrome in those 4 years of age and older. In this article, the putative mechanism of action is described, along with data relating to its pharmacokinetics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Of these, 588 publications were excluded because they did not meet the inclusion criteria. The seven remaining publications were off‐topic or duplicates of studies in the Cochrane review . Thus, no articles from the literature search were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 588 publications were excluded because they did not meet the inclusion criteria. The seven remaining publications were off‐topic or duplicates of studies in the Cochrane review . Thus, no articles from the literature search were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…As phenobarbital is a common antiepileptic used in canine patients, investigation into the impact phenobarbital has on the pharmacokinetics of rufinamide in dogs is warranted. While impaired renal function has not been shown to affect rufinamide pharmacokinetics in humans, the impact hepatic insufficiency may have is not known (Ferrie, 2010). Studies are required to determine how concurrent liver or kidney disease might alter the pharmacokinetics of rufinamide.…”
Section: Discussionmentioning
confidence: 99%
“…The bioavailability of RUF is probably less than 85% and protein binding, primarily to albumin, is relatively low and ranges from 26 to 34%. 5 The t½ of RUF is approximately 6 to 10 hours. 6 RUF is metabolized primarily by carboxylesterases to an inactive metabolite (CGP 47292) and is excreted renally.…”
Section: Introductionmentioning
confidence: 99%
“…4,7 Several studies have suggested that enzyme-inducing AEDs (EIAEDs) can increase the clearance and decrease the concentration of RUF. 4,5,7 The primary aim of this study was to examine the influence of age and type of concomitant AEDs on the clearance of RUF and to examine the influence of RUF on the clearance of concomitant AEDs in children with epilepsy. The secondary aim was to evaluate the efficacy and adverse events of RUF in the study group.…”
Section: Introductionmentioning
confidence: 99%